2007
DOI: 10.1152/ajpcell.00467.2006
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active lipids promote trafficking and membrane association of Rac1 in insulin-secreting INS 832/13 cells

Abstract: McDonald P, Veluthakal R, Kaur H, Kowluru A. Biologically active lipids promote trafficking and membrane association of Rac1 in insulin-secreting INS 832/13 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…In an attempt to identify precise regulatory mechanisms involved in glucose-mediated activation of Rac1 and insulin secretion, we first proposed [22] and subsequently confirmed experimentally [23] that certain biologically-active lipid second messengers [e.g., PA, PIP 2 ] promote dissociation of Rac1 from Rac1/GDI complex to facilitate activation of Rac1 in rodent islets and clonal β-cells. Therein, we also proposed that Arf6 could represent one of the upstream regulators of Rac1 activation by generating relevant lipid second messengers via phospholipase activation to dissociate the Rac1/GDI complex [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to identify precise regulatory mechanisms involved in glucose-mediated activation of Rac1 and insulin secretion, we first proposed [22] and subsequently confirmed experimentally [23] that certain biologically-active lipid second messengers [e.g., PA, PIP 2 ] promote dissociation of Rac1 from Rac1/GDI complex to facilitate activation of Rac1 in rodent islets and clonal β-cells. Therein, we also proposed that Arf6 could represent one of the upstream regulators of Rac1 activation by generating relevant lipid second messengers via phospholipase activation to dissociate the Rac1/GDI complex [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Rac1 has been shown to control multiple cellular processes, including actin/microtubule cytoskeleton organisation (Colley, 2000), reactive oxygen species (ROS) generation (Bishop and Hall, 2000; Whaley-connell et al , 2007), membrane trafficking (McDonald et al , 2007), hypoxia-stimulated breast cancer cell migration (Han et al , 2008; Vermeulen et al , 2010), cell adhesion and migration (Nobes and Hall, 1999; Kraynov et al , 2000; Ridley, 2001), and cell proliferation (Benitah et al , 2004; Choi et al , 2009). Because Rac1 is also a member of the NADPH oxidase, which generates ROS (Bokoch and Diebold, 2002), it regulates NADPH oxidase complex assembly in most cells (Diebold, et al , 2009), and it has been shown to be a critical determinant of intracellular redox status.…”
mentioning
confidence: 99%
“…8). We propose that glucose-induced activation of PLD leads to the generation of biologically active lipids, which, in turn, regulate G-protein (e.g., Rac1) function by dissociating Rac1 from its inhibitory GDI [10]. It is also likely that glucose-induced, Arf6-mediated ERK1/2 activation facilitates Rac1 activation as we have demonstrated recently [6,26].…”
Section: Discussionmentioning
confidence: 67%